(untitled) (Journal of Guidance and Counselling Studies, 2021)
In recent years, researchers have attempted to study the mentally retarded using a wide variety of paradigms. This reading is an attempt to present a comprehensive synopsis of some current social, medical, and psychological and educational attitudes to the mentally retarded and subnormal. The paper concludes by arguing that the ambit and precinct of mentally retarded and subnormal pose some central ethical issues which need to be faced by society thus pointing the way towards plans for the future in this realm of enquiry.